Pengaruh Brand Image & Kualitas Produk Terhadap Keputusan Pembelian Smartphone Oppo dengan Country of Origin Sebagai Variabel Moderating - Shania Mega Oktavia Sinaga; Rakhmawati Purba; Lira Mustika Sari (STIE Bina Karya, 2023)
The many types and brands of smartphones offered in the market make consumers have a variety of choices and of course this also greatly encourages manufacturers to sell their products with good quality and standard prices. This study aims to determine the effect of Brand Image & Product Quality on Purchasing Decisions of Oppo Smartphones with Country Of Origin as a Moderating Variable in Bandar Sono Village, Tebing Tinggi City. This type of quantitative descriptive research, taking samples from neighborhood 1 people who use Oppo brand cellphones with the Cochran formula so that the sample is 96 people. The side technique used is purposive sampling. The data obtained from distributing the questionnaires was processed using the SPSS tool. The tests carried out are instrument tests, classical assumption tests, multiple linear regression, determinant coefficients and hypotheses with partial tests and residual tests. The results of this study prove that: brand image and product quality influence the purchasing decision of an Oppo Smartphone. Country of Origin can moderate the relationship between Brand Image and purchasing decisions and Country of origin cannot moderate the relationship between product quality and purchasing decisions for Oppo Smartphones in Bandar Sono Village, Tebing Tinggi City.